Screening and identification of lactic acid bacteria with α-glucosidase inhibiting activity - Liu, Yi; Yang, Zixian; Liu, Ang; Dong, Boyu; Yao, Qiuping; Ran, Xinglin; Zhu, Dequan (Frontiers in Microbiology, 2025)
In this study, lactic acid bacteria were isolated from traditional fermented foods in Guizhou. The fermentation supernatant and cell disruption extract were used to screen lactic acid bacteria with α-glucosidase inhibitory activity, and the active lactic acid bacteria strains with potential hypoglycemic effect were screened. The results showed that 10 strains were screened from 27 strains of lactic acid bacteria with α-glucosidase inhibitory activity, of which 5 strains had good acid and bile salt tolerance. The best acid resistance was XG01, and the survival rate was as high as 98.5%. ST01 had the strongest tolerance to bile salt, up to 77.3%. The lactic acid bacteria cell extracts of HLG01, YR01, ST01 and XG01 could better inhibit the activity of α-glucosidase, and the inhibition rates were 39.27, 38.6, 38.53, and 34.4%, respectively. The fermentation supernatant of JR01 could better inhibit the activity of α-glucosidase, and the inhibition rate reached 33.8%. Through molecular biological identification, HLG01, YR01, and ST01 were were Lactiplantibacillus plantarum, XG01 was Pediococcus pentosaceus, and JR01 was Weissella cibaria. Weissella cibaria JR01 is the first reported lactic acid bacterium with α-glucosidase inhibitory activity. Five strains of lactic acid bacteria with good tolerance were screened out, which provided a strain basis for the subsequent study of the hypoglycemic effect of lactic acid bacteria and the development of various functional foods.